Transforming meaning: Reinterpretation of Riau architectural identities (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
The study explores the reinterpretation of local architectural identities through understanding Barthes' semiotic system. After decentralisation, Indonesian provinces were encouraged to translate their local culture into their local provincial identity and integrate it within their built environment. The Riau province is largely dominated by Malay culture, imprinting such culture as the basis of Riau architectural identity. In Pekanbaru, as capital of Riau, many contemporary buildings reflect Malay traditional architecture. This paper aims to address the transformation of meaning and identities of Malay architecture in Pekanbaru, utilising Roland Barthes' semiotics approach. Using Soeman HS Library as a case study, the study conducts semiotic explorations of denotative and connotative meanings in the evolution of Malay-influenced architecture in Pekanbaru. The study discusses the culture of the Riau society as the basis of their value system, investigating how it applies to its building elements using Barthes' semiotic analysis. Such a system shapes how the associated meanings of vernacular Malay homes are understood by Riau society and then transformed into contemporary building elements.